Predictability of Working Conditions as a Prerequisite for Effective Exercise of Labour Rights: A Review of Directive (EU) 2019/1152 - Kovačević, Ljubinka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Employee, as a weaker (legally subordinate and economically dependent) party to the employment relationship, needs to be informed about working conditions in a timely and appropriate manner, especially in countries where the employment contract does not have to be concluded in writing. Providing information on working conditions to the employees, therefore, represents an important prerequisite for effective enjoyment of employment rights, because it allows them to properly assess their own employment status, and in the event of a labor dispute, makes it easier to prove the contractual working conditions. This can also contribute to the fairness of the competition on the market, as well as the suppression of undeclared work, because absence of an employer's written notice regarding working conditions can serve as an indicator, to the labor inspection and other relevant authorities, of violation of labor rights in a particular entreprise. Although an employer's obligation to inform workers about working conditions is regulated in detail by the Council Directive 91/533/EEC at the EU level, many workers are denied written notice, due to, amongst other things, the emergence of new forms of employment that are heavily associated with the risk of difficulty in exercising labor rights. Directive (EU) 2019/1152 of the European Parliament and of the Council of 20 June 2019 on transparent and predictable working conditions in the European Union, which is applied to the new forms of employment, as well as to bogus self-employment seeks to overcome this risk, and, in addition to expanding the circle of persons who have to be notified, it also establishes the catalog of minimum rights of all workers. Therefore, the article critically discusses the key solutions from the new directive, pointing out the risk that such a wide circle of protected persons may deter employers from establishing employment, as well as from consistent application of relevant (labor law, social law and tax law) regulations.
Keywords: working conditions; informing of employee; new forms of work; European Union law.